A pandemic of hate: Social representations of COVID‐19 in the media. Issue 1 (13th January 2022) - Ittefaq, Muhammad; Abwao, Mauryne; Baines, Annalise; Belmas, Genelle; Kamboh, Shafiq Ahmad; Figueroa, Ever Josue
Abstract: Since the COVID‐19 pandemic started, Asians, particularly those in Chinese communities, have faced increased discrimination and overt racism in addition to the virus itself. In this study, the authors examined social representations of COVID‐19 in mainstream newspapers. We evaluated 451 articles from three major publications representing three countries: China, the United States, and the United Kingdom. A qualitative thematic analysis, conducted through the lens of social representations theory (SRT) and its concept of cognitive polyphasia, revealed four major themes: (a) the virus' portrayal as a threat; (b) the racialization of COVID‐19 as a multi‐faceted threat; (c) calls for collectivization to curb the racialization of the virus; and (d) speculative solutions to end discrimination against Asians. Our results suggest that print media emphasize the idea that global efforts must be made to change how people think about, talk about, and understand the COVID‐19 pandemic.